The Jewish Identity of the “Unexpected Generation” in the Context of the Upbringing Model in a Mixed Family - Joanna Cukras-Stelągowska (Colloquia Humanistica, 2020)
The Jewish Identity of the “Unexpected Generation” in the Context of the Upbringing Model in a Mixed Family